Bone Regeneration after Treatment with Covering Materials Composed of Flax Fibers and Biodegradable Plastics: A Histological Study in Rats. (11th August 2016) - Gredes, Tomasz; Kunath, Franziska; Gedrange, Tomasz; Kunert-Keil, Christiane
Abstract : The aim of this study was to examine the osteogenic potential of new flax covering materials. Bone defects were created on the skull of forty rats. Materials of pure PLA and PCL and their composites with flax fibers, genetically modified producing PHB (PLA-transgen, PCL-transgen) and unmodified (PLA-wt, PCL-wt), were inserted. The skulls were harvested after four weeks and subjected to histological examination. The percentage of bone regeneration by using PLA was less pronounced than after usage of pure PCL in comparison with controls. After treatment with PCL-transgen, a large amount of new formed bone could be found. In contrast, PCL-wt decreased significantly the bone regeneration, compared to the other tested groups. The bone covers made of pure PLA had substantially less influence on bone regeneration and the bone healing proceeded with a lot of connective tissue, whereas PLA-transgen and PLA-wt showed nearly comparable amount of new formed bone. Regarding the histological data, the hypothesis could be proposed that PCL and its composites have contributed to a higher quantity of the regenerated bone, compared to PLA. The histological studies showed comparable bone regeneration processes after treatment with tested covering materials, as well as in the untreated bone lesions.